USING A FIRST-ORDER-BASED LANGUAGE TO AUTOMATICALLY SYNTHESIZE VALID ARGUMENTS OF PROPOSITIONAL CALCULUS - Oliveira, Elthon; Campus Arapiraca Universidade Federal de Alagoas (2023)
The elaboration of problems with common specific characteristics is considered a tedious task on the part of the teacher. In the context of Logic discipline, this article presents an approach designed for generating propositional calculus formulas and valid arguments. Such a process occurs according to parameters customized by the user. This work adapts the technique of Sketch Generation from Program Synthesis, which is used in conjunction with constraint programming in the Alloy modeling language to make formulas and arguments generation possible. Resources capable of generating elements based on parameters supplied by the user were developed in the form of a mobile app. Such an app hides from the user all the complexity of the process.